Creation of an Electronic Real Estate Database Based on Orthophotos and Geographic Information Systems - Aliyev, E.M.; Maharramli, Z.S. (Herald of Azerbaijan Engineering Academy, 2024)
Using orthophotos and geoinformation technologies, the electronic database (EDD) of spatial information of the Surakhani district of Baku was created. The issues of managing spatial objects using the capabilities of GIS and creating digital databases for resolving property issues are considered using the example of the Surakhani region.